ENHANCING STUDENTS’ CRITICAL READING SKILLS THROUGH GROUP DISCUSSION IN COOPERATIVE LEARNING - Idha Nurhamidah (Dinamika Bahasa dan Budaya, 2014)
This  study aims to find out whether or not group discussion is effective to enhance  students’ critical reading  ability. The subjects were 64 students who were divided  into two groups; one consisting of 32 students assigned as the experimental group, and the other consisting of 32 students as the control group. The experimental group studied critical reading through group discussion while  the control group studied critical reading through a conventional way.  Both groups were taught for 12 sessions, each lasting for 90 minutes. The data were collected by means of critical reading test. In the study, it was hypothesized that there was a significant difference between the critical reading  ability of the students taught by employing  group discussion  activities and those taught employing a conventional way. The result of the t-test was 5.84 while the t-table was 3.6. It indicated that group discussion activities had improved the students’ critical reading  ability significantly. Key words: academic reading, critical reading